Low-loss optical fiber and preparation method thereof

By co-doping the core of chlorine and bromine, the problem of limited effects of existing optical fibers in reducing the imaginary temperature is solved, the refractive index and attenuation rate are improved, and the application needs of low-loss optical fibers are met.

CN119689630APending Publication Date: 2025-03-25HENGTONG OPTICAL MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856841.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing silica glass fibers have limited effects in reducing imaginary temperatures, making it difficult to meet the strict requirements for material performance in certain specific application scenarios. At the same time, the deep doping of fluorine-based processes increase production costs and may affect material performance.

Method used

By co-doping the core with chlorine and bromine, both of them not only reduce the imaginary temperature, but also significantly improve the refractive index, meeting the application needs of low-attenuation optical fibers.

Benefits of technology

It is achieved to significantly reduce the imaginary temperature without significantly affecting the refractive index, improve the thermal stability and transmission efficiency of the optical fiber, simplify the process and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119689630A_ABST
    Figure CN119689630A_ABST
Patent Text Reader

Abstract

The invention provides a low-loss optical fiber and a preparation method thereof, the low-loss optical fiber comprises a fiber core part of a central shaft and an outer sleeve surrounding the fiber core part, the refractive index of the area of the outer sleeve is lower than that of the area of the fiber core part, the fiber core part is co-doped with a chlorine element and a bromine element, and the total content of doped elements in the fiber core part is 2wt%-5wt%; according to the low-attenuation optical fiber, chlorine and bromine are co-doped on the fiber core part, so that the hypothetical temperature is reduced, the refractive index is obviously improved, and meanwhile, the application requirement of the low-attenuation optical fiber is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-loss optical fibers, and in particular to a low-loss optical fiber and a preparation method thereof. Background Art

[0002] In the broad field of optical material science, silica glass has become the core material for cutting-edge technology products such as optical fiber communications, precision optical components and high-precision sensors due to its excellent optical properties and chemical stability. In these high-tech applications, the fictive temperature (as a key indicator of the thermal stability of the material) and the refractive index of silica glass are two indispensable parameters for evaluating its comprehensive performance.

[0003] In order to further improve these key properties, researchers have long been committed to exploring efficient doping technologies, aiming to achieve deep optimization of its performance by precisely controlling the composition of doping elements in silica glass. However, the traditional single dopant strategy has shown relatively limited effects in reducing the fictive temperature, and it is difficult to fully meet the stringent requirements of material performance in certain specific application scenarios. Therefore, how to develop a more efficient doping strategy to significantly reduce the fictive temperature without significantly affecting the refractive index has become a technical problem that needs to be overcome in this field.

[0004] In recent years, with the continuous deepening of research, the co-doping technology of chlorine (Cl) and fluorine (F) has emerged, opening up a new path for the performance optimization of silica glass. In this innovative system, chlorine and fluorine elements each play their own roles, forming a unique performance regulation mechanism: the introduction of chlorine helps to increase the refractive index, while fluorine plays a corresponding role in reducing it. The two check and balance each other to ensure the stability of the overall refractive index of silica glass. More importantly, the chlorine and fluorine co-doping strategy significantly reduces the fictive temperature, providing a new solution for improving the thermal stability of silica glass.

[0005] Although the chlorine and fluorine co-doping technology has shown significant advantages, it still faces certain challenges in practical applications. In particular, in the process of maintaining the stability of the optical waveguide structure, the cladding part usually needs to be deeply doped with fluorine to ensure a suitable relative refractive index difference with the core. However, this deep doping process not only increases production costs, but may also have an adverse effect on the overall performance of the material, limiting its application in a wider range of fields.

[0006] In addition, in the process of preparing Ge-doped and chlorine-doped core glass rods by VAD deposition process, although chlorine doping can reduce the concentration factor fluctuation caused by Ge doping to a certain extent, this process is still difficult to completely eliminate the Rayleigh scattering problem caused by Ge. After the sintered core rod is sheathed into an optical fiber preform rod and subjected to drawing, the attenuation coefficient of the obtained optical fiber in the 1550nm band is still high (>0.170dB / km), which cannot meet the application requirements of low-attenuation optical fiber. In the existing patent CN114397727A, fluorine has a smaller polarizability, and the binding energy of the Si-F bond is much greater than the binding energy of the Si-O bond, the overall polarizability of silica is reduced, and the refractive index is reduced. Silica glass is co-doped with chlorine and fluorine, in which chlorine plays a role in increasing the refractive index, while fluorine plays a role in reducing the refractive index. The two offset each other, and the overall pure Si core refractive index structure is shown. The cladding must ensure that fluorine is deeply doped to obtain the refractive index difference required for effective waveguide between the core layer and the cladding, and ensure a suitable relative refractive index to maintain an optical waveguide structure. This process is relatively complex and costly, which limits its widespread application in actual production.

[0007] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application, nor does it necessarily provide technical guidance. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0008] In order to solve the above technical problems, the present invention proposes a low-loss optical fiber and a preparation method thereof. By co-doping the core with chlorine and bromine, both of them not only reduce the fictive temperature, but also have a significant effect on improving the refractive index, while meeting the application requirements of low-attenuation optical fiber.

[0009] In order to achieve the above object, the technical solution of the present invention is as follows:

[0010] The present invention provides a low-loss optical fiber, comprising: a core portion of a central axis and an outer sheath surrounding the core portion, wherein the refractive index of the outer sheath region is lower than the refractive index of the core portion region, the core portion is co-doped with chlorine and bromine elements, and the total content of doped elements in the core portion is 1.5wt% to 5wt%.

[0011] The present invention proposes a low-loss optical fiber and a preparation method thereof. By co-doping the fiber core with chlorine and bromine, both of them not only reduce the fictive temperature, but also have a significant effect of improving the refractive index, while meeting the application requirements of low-attenuation optical fiber.

[0012] As a preferred technical solution, the bromine doping content in the core portion accounts for 0.1 to 40% of the total content of doping elements.

[0013] As a preferred technical solution, the outer cladding tube includes: an inner cladding and an outer cladding surrounding the inner cladding, the refractive index of the inner cladding region is lower than the refractive index of the core region, and the refractive index of the outer cladding region is higher than the refractive index of the inner cladding region and lower than the refractive index of the core region.

[0014] As a preferred technical solution, the inner cladding includes: fluorine-doped silica glass and / or bromine-doped silica glass, and the outer cladding includes: fluorine-doped silica glass.

[0015] As a preferred technical solution, the relative refractive index difference Δ1 of the core region is 0% to 0.3%, and the radius R1 of the core region is 5 to 15 μm; the relative refractive index difference Δ2 of the inner cladding region is 0 to -0.25%, and the radius R2 of the inner cladding region is 15 to 45 μm; the relative refractive index difference Δ3 of the outer cladding region is 0 to -0.15%, and the radius R3 of the outer cladding region is 40 to 120 μm.

[0016] As an optimal technical solution, the difference between the relative refractive index difference △2 of the inner cladding region and the relative refractive index difference △1 of the core region is 0.2% to 0.4%, and the difference between the relative refractive index difference △3 of the outer cladding region and the relative refractive index difference △1 of the core region is 0.1% to 0.4%.

[0017] As a preferred technical solution, the attenuation coefficient of the optical fiber at a wavelength of 1550nm is ≤0.165dB / km, and the mode field diameter of the optical fiber at a wavelength of 1550nm is 12.0um-13.0μm.

[0018] The present invention also provides a method for preparing a low-loss optical fiber, and the method comprises the following steps:

[0019] S1 uses vapor phase axial deposition process to prepare SiO 2 substrate, to obtain SiO 2 Base material;

[0020] S2 will be S iO 2 The substrate was exposed to SiBr 4 Dopant precursors and SiCl 4 In the mixed atmosphere of dopant precursor, SiO 2 Before the substrate is fully densified, 2 The substrate body is doped, and finally sintered to densify, and annealed to obtain a chlorine and bromine co-doped core portion;

[0021] S3: inserting the fiber core part co-doped with chlorine and bromine into an outer sheath to obtain an optical fiber preform rod that can be used for drawing, and drawing the optical fiber preform rod that can be used for drawing to form a low-loss optical fiber.

[0022] As a preferred technical solution, in step S2, SiO 2 The substrate was exposed to SiBr 4 Dopant precursors and SiCl 4 The doping time in the mixed atmosphere of the dopant precursor is 1 to 1.5 hours.

[0023] As a preferred technical solution, in step S3, the optical fiber preform rod available for drawing is drawn at a drawing speed of 1000m / min to 2000m / min, and the drawing tension is 150g to 200g.

[0024] The present invention provides a low-loss optical fiber and a preparation method thereof, which have the following beneficial effects:

[0025] 1) By co-doping the fiber core with chlorine and bromine, both of them not only reduce the fictive temperature, but also significantly increase the refractive index, while meeting the application requirements of low-attenuation optical fiber;

[0026] 2) Through the co-doping of chlorine and bromine, they can work together on the microstructure of the optical fiber material to reduce the thermal motion energy inside it, which is manifested as a decrease in the fictive temperature. This helps to improve the stability of the optical fiber in a high temperature environment and reduce the optical signal attenuation caused by thermal effects;

[0027] Co-doping of chlorine and bromine can change the electron cloud distribution and polarization characteristics of optical fiber materials, thereby increasing their refractive index. The increase in refractive index helps to enhance the confinement of optical signals in optical fibers, reduce the leakage and scattering of optical signals, and thus improve the transmission efficiency of optical fibers.

[0028] Chlorine and bromine co-doping, because the atomic radius of chlorine and bromine is larger than that of fluorine, the effect of reducing the fictive temperature is better than that of chlorine and fluorine co-doping, and the cladding does not need to be deeply doped with fluorine to obtain the refractive index difference required for effective waveguide between the core layer and the cladding. The reason why chlorine and bromine co-doping is better than chlorine and fluorine co-doping in reducing the fictive temperature is mainly because the atomic radius of chlorine and bromine is larger than that of fluorine, which can disturb the original lattice structure and change the electron cloud distribution to a greater extent. Since the electronegativity of chlorine and bromine is smaller than that of fluorine, the degree of overlap between their electron clouds and silicon atoms is greater, which helps to reduce the electronic transition energy of the material. The reduction of electronic transition energy is also an important factor leading to the reduction of fictive temperature;

[0029] At the same time, due to the superior performance of co-doping with chlorine and bromine in improving the refractive index, the cladding no longer needs to be deeply doped with fluorine to further adjust the refractive index difference, which simplifies the process and reduces costs.

[0030] 3) The synergistic effect of bromine and chlorine can further enhance the performance of optical fiber. For example, co-doping with chlorine and bromine can reduce the fictive temperature of optical fiber and improve the thermal stability of optical fiber; at the same time, co-doping with chlorine and bromine can also optimize the attenuation characteristics of optical fiber, making it have a lower attenuation rate within a specific wavelength range.

[0031] 4) The outer cladding tube comprises: an inner cladding and an outer cladding surrounding the inner cladding, the refractive index of the inner cladding region is lower than the refractive index of the core region, and the refractive index of the outer cladding region is higher than the refractive index of the inner cladding region and lower than the refractive index of the core region; the refractive index of the inner cladding is lower than the refractive index of the core region. Such a design can limit the propagation of the pump light within the core layer, avoid the pump light from directly leaking to the outside of the optical fiber, and thus improve the utilization rate of the pump light.

[0032] 5) Fluorine-doped silica glass has a lower refractive index, which helps to confine the pump light to the area between the inner cladding and the core, thereby improving the utilization of the pump light;

[0033] Bromine-doped silica glass may have a refractive index close to or slightly lower than that of the fiber core, which helps to cooperate with other doping elements (such as chlorine) to jointly regulate the refractive index distribution of the optical fiber to achieve better optical fiber performance;

[0034] Fluorine-doped silica glass is used as the outer cladding material, and its refractive index is lower than that of the core but higher than that of the inner cladding. This design can provide a suitable waveguide structure, and the bound light propagates only between the core and the inner cladding, ensuring that the optical signal is propagated with minimal loss.

[0035] 6) The relative refractive index difference Δ1 in the core region is 0% to 0.3%. An appropriate Δ1 value can also optimize the bandwidth and dispersion characteristics of the optical fiber, so that it has better transmission performance within a specific wavelength range.

[0036] The radius R1 of the core area is 5 to 15 μm. In single-mode optical fiber, the size of R1 is usually precisely controlled within a certain range to ensure that the optical signal is transmitted in a single mode in the core, thereby improving the transmission quality and stability of the optical fiber.

[0037] The relative refractive index difference Δ2 of the inner cladding region is 0 to -0.25%, and the relative refractive index difference Δ2 of the inner cladding region is lower than that of the core region, which helps to confine the pump light to the region between the inner cladding and the core, thereby improving the utilization rate of the pump light. At the same time, the negative value design of Δ2 can also prevent the optical signal from leaking from the core into the inner cladding, thereby further improving the transmission efficiency of the optical fiber.

[0038] The radius R2 of the inner cladding region is 15 to 45 μm. The radius R2 of the inner cladding region determines the macrobending loss of the pump light. A larger R2 value can provide a wider pump light transmission space, which is conducive to achieving an efficient optical pumping process and avoiding the escape of light from the cladding. At the same time, the size of R2 also affects the mechanical properties and stability of the optical fiber. By reasonably designing the R2 value, it can be ensured that the optical fiber will not be damaged during the transmission process.

[0039] The relative refractive index difference Δ3 of the outer cladding region is 0 to -0.15%, and the relative refractive index difference Δ3 of the outer cladding region is further lower than that of the inner cladding region, which helps to form a stable optical waveguide structure and ensures effective transmission of pump light in the optical fiber;

[0040] At the same time, the negative value design of Δ3 can also enhance the corrosion resistance and mechanical strength of the optical fiber, and improve the service life and stability of the optical fiber.

[0041] The radius R3 of the outer cladding region is 40 to 120 μm. The size of R3 also affects the coupling efficiency between the optical fiber and light sources, receivers and other devices. By reasonably designing the R3 value, good matching and connection between the optical fiber and other devices can be ensured.

[0042] 7) When the difference between Δ2 and Δ1 is in the range of 0.2% to 0.4%, when the difference between Δ2 and Δ1 is moderate, the transmission path of the pump light between the inner cladding and the core can be optimized, and the absorption efficiency of the pump light can be improved.

[0043] 8) When the difference between Δ3 and Δ1 is in the range of 0.1% to 0.4%, the leakage of optical signals from the core region to the outer cladding region can be effectively reduced. This is because the refractive index of the outer cladding is lower than that of the core region, and the difference between the two is moderate, which can form an effective optical signal constraint; reducing optical signal leakage means that more optical signals can be transmitted in the core region, thereby improving the transmission efficiency of optical signals; this is especially important for long-distance, high-speed optical fiber communications.

[0044] 9) The attenuation coefficient is an important indicator to measure the degree of loss of optical signals during transmission in optical fibers. When the attenuation coefficient is small, it means that the loss of optical signals during transmission in optical fibers is also small. Therefore, an attenuation coefficient of ≤0.165dB / km at a wavelength of 1550nm helps reduce the loss of optical signals during transmission and improves the transmission efficiency of optical signals. A smaller attenuation coefficient means that optical signals can maintain higher intensity over longer distances. Therefore, this type of optical fiber can be used to build long-distance optical fiber communication systems to achieve long-distance, high-speed data transmission.

[0045] 10) The size of the mode field diameter directly affects the coupling efficiency. When the profile of the incident light beam is closer to a Gaussian shape and its beam waist diameter is equal to or close to the mode field diameter of the optical fiber, the coupling efficiency is higher. Therefore, a mode field diameter of 12.0μm to 13.0μm helps to optimize the coupling process of the optical signal and reduce the loss of the optical signal. The mode field diameter is closely related to the mode dispersion of the optical fiber. Mode dispersion will cause the optical signal to disperse during transmission, thereby reducing the transmission efficiency. A smaller mode field diameter helps to reduce mode dispersion, allowing the optical signal to maintain better coherence and stability during transmission.

[0046] 11) Fictitious temperature is a parameter closely related to optical fiber attenuation. It reflects the thermal motion state of the microstructure inside the optical fiber. Lowering the fictitious temperature means reducing the thermal motion of the microstructure inside the optical fiber, thereby reducing the scattering and attenuation caused by thermal motion.

[0047] SiO prepared by vapor phase axial deposition process 2 The substrate has high purity and uniformity, which reduces the scattering and attenuation caused by impurities and defects, thereby indirectly reducing the fictive temperature;

[0048] In SiO 2 Chlorine and bromine are doped into the matrix. These doping elements can change the microstructure inside the optical fiber, reduce the scattering and attenuation caused by thermal motion, and at the same time, the doping treatment can also optimize the refractive index distribution of the optical fiber and further reduce the attenuation.

[0049] Chlorine and bromine as dopants can change SiO 2 The refractive index of the substrate, these doping elements have appropriate atomic numbers and electronic structures, and can react with SiO 2 The substrate forms stable chemical bonds, thus changing its refractive index;

[0050] By precisely controlling the doping concentration, the refractive index can be precisely regulated. The appropriate doping concentration can balance the increase in refractive index and the reduction in attenuation, thereby meeting the application requirements of low-attenuation optical fibers.

[0051] High quality SiO 2The substrate and precise doping treatment can reduce the scattering and attenuation sources inside the optical fiber, thereby reducing attenuation; during the drawing process, by precisely controlling parameters such as drawing speed and temperature, the stability of the optical fiber's microstructure and refractive index distribution can be maintained, further reducing attenuation. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 A schematic diagram of the cross-sectional structure of a low-loss optical fiber provided by the present invention;

[0053] Figure 2 A schematic diagram of the relative refractive index distribution of a low-loss optical fiber provided by the present invention;

[0054] Among them: 1-core part of the central axis; 2-inner cladding; 3-outer cladding. DETAILED DESCRIPTION

[0055] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0056] like Figure 1 As shown, the present invention provides a low-loss optical fiber, comprising: a core portion of a central axis and an outer sheath surrounding the core portion, the refractive index of the outer sheath region is lower than the refractive index of the core portion region, the core portion is co-doped with chlorine and bromine elements, and the total content of doped elements in the core portion is 2wt% to 5wt%.

[0057] The present invention proposes a low-loss optical fiber and a preparation method thereof. By co-doping the fiber core with chlorine and bromine, both of them not only reduce the fictive temperature, but also have a significant effect of improving the refractive index, while meeting the application requirements of low-attenuation optical fiber.

[0058] The dopant will break the Si-O bond inside the silica glass and replace it with a SiX bond, breaking the silica glass network structure and causing rearrangement. The new composition structure is more open, resulting in a decrease in the viscosity of the silica glass. In this experiment, by doping the silica glass with 2wt% chlorine and 0-1wt% bromine, the fictive temperature of the silica glass is reduced by 100-200°C, and the difference with the fictive temperature of the inner fluorine-doped layer is less than 30°C, so that during high-temperature drawing, the viscosity of the inner cladding and the core is basically the same, avoiding the large viscosity difference between the inner cladding and the core. In the fiber drawing process, the optical fiber preform is usually heated to the softening point or close to the softening point. Due to the different doping components, the viscosity of the outer sheath and the core is different. The viscosity difference will generate stress at the core and the outer sheath. Therefore, good viscosity matching will reduce the internal stress generated at the interface between the core and the outer sheath, reduce the Rayleigh scattering effect, thereby reducing the loss of light in the core and reducing attenuation.

[0059] The total content of doping elements in the core portion is preferably 2wt%, 3wt%, 4wt% and 5wt%. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values ​​included in the range.

[0060] Preferably, the bromine doping content in the core portion accounts for 0.1% to 40% of the total content of doping elements, and the bromine doping content in the core portion accounts for 0.1%, 10%, 20%, 30% and 40% of the total content of doping elements. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0061] Preferably, the outer cladding tube comprises: an inner cladding and an outer cladding surrounding the inner cladding, the refractive index of the inner cladding region is lower than the refractive index of the core region, and the refractive index of the outer cladding region is higher than the refractive index of the inner cladding region and lower than the refractive index of the core region.

[0062] Preferably, the inner cladding comprises: fluorine-doped silica glass and / or bromine-doped silica glass.

[0063] Preferably, the outer cladding comprises: fluorine-doped silica glass.

[0064] Preferably, if Figure 2As shown, the relative refractive index difference Δ1 of the core region is 0% to 0.3%, and the relative refractive index difference Δ1 of the core region is preferably 0%, 0.1%, 0.2% and 0.3%. Due to space limitations and simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the radius R1 of the core region is 5 to 15 μm, and the radius R1 of the core region is preferably 5 μm, 10 μm and 15 μm. Due to space limitations and simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the relative refractive index difference Δ2 of the inner cladding region is 0 to -0.25%, and the relative refractive index difference Δ2 of the inner cladding region is preferably 0%, -0.05%, -0.1%, -0.15%, -0.2% and -0.25%. Due to space limitations and simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the radius R2 of the inner cladding region is 1 The radius R2 of the inner cladding region is preferably 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm and 45 μm. Due to space limitations and for simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the relative refractive index difference Δ3 of the outer cladding region is 0 to -0.15%, and the relative refractive index difference Δ3 of the outer cladding region is preferably 0%, -0.05%, -0.1% and -0.15 %, due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the radius R3 of the outer cladding region is 40-120μm, and the radius R3 of the outer cladding region is preferably 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm and 120μm. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0065] Preferably, the difference between the relative refractive index difference △2 of the inner cladding region and the relative refractive index difference △1 of the core region is 0.2% to 0.4%, and the difference between the relative refractive index difference △2 of the inner cladding region and the relative refractive index difference △1 of the core region is preferably 0.2%, 0.3% and 0.4%. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0066] Preferably, the difference between the relative refractive index difference △3 of the outer cladding and the relative refractive index difference △1 of the core region is 0.1% to 0.4%, and the difference between the relative refractive index difference △3 of the outer cladding and the relative refractive index difference △1 of the core region is preferably 0.1%, 0.2%, 0.3% and 0.4%. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0067] Preferably, the attenuation coefficient of the optical fiber at a wavelength of 1550nm is ≤0.165dB / km, and the attenuation coefficient of the optical fiber at a wavelength of 1550nm is preferably 0.165dB / km, 0.15dB / km, 0.1dB / km, 0.05dB / km. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0068] Preferably, the mode field diameter of the optical fiber at a wavelength of 1550nm is 12.0um to 13.0μm, and the mode field diameter of the optical fiber at a wavelength of 1550nm is preferably 12.0um, 12.5μm and 13.0μm. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0069] The present invention also provides a method for preparing a low-loss optical fiber, and the method comprises the following steps:

[0070] S1 uses vapor phase axial deposition process to prepare SiO 2 substrate, to obtain SiO 2 Base material;

[0071] S2 will be S iO 2 The substrate was exposed to SiBr 4 Dopant precursors and SiCl 4 The doping treatment is carried out for 1 to 1.5 hours in the mixed atmosphere of the dopant precursor. 2 Before the substrate is fully densified, 2 The substrate body is doped, and finally sintered to densify, and annealed to obtain a chlorine and bromine co-doped core portion;

[0072] S3: inserting the fiber core part co-doped with chlorine and bromine into an outer sheath to obtain an optical fiber preform rod that can be used for drawing, and drawing the optical fiber preform rod that can be used for drawing to form a low-loss optical fiber.

[0073] Preferably, in step S3, the optical fiber preform rod available for drawing is drawn at a drawing speed of 1000 m / min to 2000 m / min, and the drawing tension is 150 g to 200 g.

[0074] The chlorine and bromine co-doped core portion is preferably a bubble-free and crystal-free transparent glass rod.

[0075] Step S1 uses a vapor phase axial deposition process to prepare SiO 2 Substrate, obtain SiO 2 The substrate specifically comprises the following steps:

[0076] S101 uses 3000g with a density of 0.35g / cm 3SiO 2 The substrate can be deposited by vapor axial deposition (VAD) process. 2 The substrate is deposited to a length of 1000 mm or more SiO 2 Base material;

[0077] S102 deposits the SiO 2 The substrate is dried by a dehydrating agent, and the dehydrating agent can be C l 2 、SiCl 4 One or two of these to obtain dried SiO 2 Base material;

[0078] S103 will dry SiO 2 The substrate is loaded into the sintering furnace and the SiO2 is preheated in the sintering furnace at a temperature of 1100°C. 2 The substrate was then heated for 30 minutes and then 5% Cl 2 、SiCl 4 The samples were dried for 2 hours in a mixed atmosphere of 95% helium to remove the effects of water and metal impurities, including 5% C l 2 、SiCl 4 C l 2 and SiCl 4 The ratio is 1:1.

[0079] The sintering and densification temperature in step S2 is 1400-1430°C.

[0080] In step S2, SiO 2 Before the substrate is fully densified, 2 The time for the doping treatment of the substrate body is 1 to 1.5 hours.

[0081] Example 1

[0082] The present invention provides a method for preparing a low-loss optical fiber, comprising the following steps:

[0083] S1 uses 3000g with a density of 0.35g / cm 3 SiO 2 The substrate can be deposited by vapor axial deposition (VAD) process to form SiO 2 The substrate is deposited to a length of 1000 mm. 2 Base material;

[0084] S2 will deposit the completed SiO 2 The substrate is made of SiCl 4 The dehydrating agent is used to dry the dried SiO 2 Base material;

[0085] S3 will dry SiO 2 The substrate is loaded into the sintering furnace and the SiO2 is preheated in the sintering furnace at a temperature of 1100°C. 2 The substrate was then heated for 30 minutes and then 5% Cl 2 、S i C l 4 The samples were dried for 2 hours in a mixed atmosphere of 95% helium to remove the effects of water and metal impurities, including 5% C l 2 、S i C l 4 C l 2 and SiCl 4 The ratio is 1:1;

[0086] S4 was then heated to 1250°C at a heating rate of 8°C / min to 2 The substrate was exposed to SiBr 4 Dopant precursors and SiCl 4 Doping treatment is performed in a mixed atmosphere of a dopant precursor for 1 hour;

[0087] After S5, in S i C l 4 The temperature was raised at a rate of 5°C / min in an atmosphere, and when the peak temperature reached 1400°C, the doped SiO 2 The substrate is completely sintered, densified and clarified, and after annealing, a chlorine and bromine co-doped core is obtained;

[0088] S6: insert the fiber core into the outer casing to obtain an optical fiber preform rod that can be used for drawing;

[0089] S7: drawing the optical fiber preform rod at a drawing speed of 1500 m / min and a drawing tension of 170 g to obtain a low-loss optical fiber;

[0090] Among them, Si Br 4 As doping precursor, SiBr 4 The boiling point is about 154℃, and liquid SiBr needs to be heated 4 Formation of vaporized SiBr 4 As doped SiO 2 The doping source of the substrate is usually liquid SiBr 4 Loaded in a stainless steel raw material tank, immersed in an oil bath and heated to 190°C, helium is usually used as a carrier gas to heat the heated evaporated Si Br 4 The gas is loaded into the sintering furnace and mixed with SiCl 4 The dopant precursor forms a mixed atmosphere and participates in the doping process in step S4.

[0091] The present invention provides a low-loss optical fiber, which is prepared according to the above method for preparing the low-loss optical fiber, wherein the bromine doping content in the core portion accounts for 26.64% of the total content of the doping elements.

[0092] Example 2

[0093] The present invention provides a method for preparing a low-loss optical fiber, comprising the following steps:

[0094] S1 uses 3000g with a density of 0.35g / cm 3 SiO 2 The substrate can be deposited by vapor axial deposition (VAD) process to form SiO 2 The substrate is deposited to a length of 1000 mm. 2 Base material;

[0095] S2 will deposit the completed SiO 2 The substrate is made of SiCl 4 The dehydrating agent is used to dry the dried SiO 2 Base material;

[0096] S3 will dry SiO 2 The substrate is loaded into the sintering furnace and the SiO2 is preheated in the sintering furnace at a temperature of 1100°C. 2 The substrate was then heated for 30 minutes and then 5% Cl 2 、S i C l 4 The samples were dried for 2 hours in a mixed atmosphere of 95% helium to remove the effects of water and metal impurities, including 5% C l 2 、S i C l 4 C l 2 and SiCl 4 The ratio is 1:1;

[0097] S4 was then heated to 1250°C at a heating rate of 8°C / min to 2 The substrate was exposed to SiBr 4 Dopant precursors and SiCl 4 Doping treatment is performed in a mixed atmosphere of a dopant precursor for 1.5 hours;

[0098] After S5, in S i C l 4 The temperature was raised at a rate of 5°C / min in an atmosphere, and when the peak temperature reached 1400°C, the doped SiO 2 The substrate is completely sintered, densified and clarified, and after annealing, a chlorine and bromine co-doped core is obtained;

[0099] S6: insert the fiber core into the outer casing to obtain an optical fiber preform rod that can be used for drawing;

[0100] S7: drawing the optical fiber preform rod at a drawing speed of 1500 m / min and a drawing tension of 170 g to obtain a low-loss optical fiber;

[0101] Among them, Si Br 4 As doping precursor, SiBr 4 The boiling point is about 154℃, and liquid SiBr needs to be heated 4 Formation of vaporized SiBr 4 As doped SiO 2 The doping source of the substrate is usually liquid SiBr 4 Loaded in a stainless steel raw material tank, immersed in an oil bath and heated to 190°C, helium is usually used as a carrier gas to heat the heated evaporated Si Br 4 The gas is loaded into the sintering furnace and mixed with SiCl 4 The dopant precursor forms a mixed atmosphere and participates in the doping process in step S4.

[0102] The present invention provides a low-loss optical fiber, which is prepared according to the above method for preparing the low-loss optical fiber, wherein the bromine doping content in the core portion accounts for 29.078% of the total content of the doping elements.

[0103] Comparative Example 1

[0104] Comparative Example 1 provides a method for preparing a low-loss optical fiber, comprising the following steps:

[0105] S1 uses 3000g with a density of 0.35g / cm 3 SiO 2 The substrate can be deposited by vapor axial deposition (VAD) process to form SiO 2 The substrate is deposited to a length of 1000 mm. 2 Base material;

[0106] S2 will deposit the completed SiO 2 The substrate is made of SiCl 4 The dehydrating agent is used to dry the dried SiO 2 Base material;

[0107] S3 will dry SiO 2 The substrate is loaded into the sintering furnace and the SiO2 is preheated in the sintering furnace at a temperature of 1100°C. 2 The substrate was then heated for 30 minutes and then 5% Cl 2 、S i C l 4 The samples were dried for 2 hours in a mixed atmosphere of 95% helium to remove the effects of water and metal impurities, including 5% C l 2、S i C l 4 C l 2 and SiCl 4 The ratio is 1:1;

[0108] S4 was then heated to 1250°C at a heating rate of 8°C / min to 2 The substrate is exposed to SiCl 4 Doping treatment is performed in a mixed atmosphere of a dopant precursor for 1 hour;

[0109] After S5, in S i C l 4 The temperature was raised at a rate of 5°C / min in an atmosphere, and when the peak temperature reached 1400°C, the doped SiO 2 The substrate is completely sintered, densified and clarified, and annealed to obtain a chlorine-doped core;

[0110] S6: insert the fiber core into the outer casing to obtain an optical fiber preform rod that can be used for drawing;

[0111] S7 draws the optical fiber preform rod at a drawing speed of 1500 m / min and a drawing tension of 170 g to obtain a low-loss optical fiber.

[0112] Comparative Example 1 provides a low-loss optical fiber, which is prepared according to the above method for preparing a low-loss optical fiber.

[0113] Experimental methods

[0114] The relative refractive index of optical fibers doped with different elements is obtained by testing with the PK2600 tester, which includes the following experimental steps:

[0115] 1) Sample preparation: The deposited SiO 2 The substrate is placed in a sintering furnace for doping with Cl or Br elements, sintering and densification, and annealing to obtain a sintered rod to be tested;

[0116] 2) Sample preparation: Cool the annealed sintered glass rod to below 40°C;

[0117] 3) Calibration instrument: pure SiO 2 The refractive index of the glass rod is set as the basic parameter standard, and the sintered rod to be tested is placed inside the PK2600 instrument.

[0118] 4) Start the instrument: After starting the instrument, the instrument will compare the pure SiO 2 The refractive index of the glass rod and the test sintered rod gives the relative refractive index difference.

[0119] 5) Recording data: The instrument uses the radial direction of the test sintered rod as the coordinate, draws the refractive index curve of the test sintered rod along the radial direction, and retains the original data;

[0120] The fictive temperature of optical fibers doped with different elements is obtained by Fourier transform infrared spectrometer testing, which specifically includes the following experimental steps:

[0121] 1) Sample preparation: Prepare the optical fiber sample to be tested into an appropriate form (such as solid) and ensure that the sample surface is clean and smooth;

[0122] 2) Calibrate the instrument: Use standard samples to calibrate the Fourier transform infrared spectrometer to ensure the accuracy and precision of the instrument;

[0123] 3) Place the sample: Place the fiber sample in the light path, usually by placing the sample on a transparent infrared window;

[0124] 4) Adjust instrument parameters: Set the instrument parameters as needed, such as scanning range, resolution, etc. These parameters may need to be adjusted according to the characteristics of the optical fiber and the purpose of the test;

[0125] 5) Start scanning: Start the Fourier infrared spectrometer and start scanning the sample. The instrument will emit an infrared beam and the sample will absorb infrared light of a specific wavelength.

[0126] 6) Record data: The instrument will draw a spectrum according to the intensity of infrared light absorbed by the sample, and record and save the spectrum data;

[0127] 7) Data analysis: Analyze the absorption characteristics of the sample based on the spectrum. If the fictive temperature of the optical fiber is related to certain characteristics of the infrared spectrum (such as the displacement of the absorption peak or the change in intensity), the fictive temperature can be inferred by analyzing the spectrum.

[0128] The correlation data between the content of different element-doped optical fibers and the relative refractive index and fictive temperature are shown in Table 1 below, the refractive index profile parameters of Comparative Example 1 and Examples 1-2 are shown in Table 2 below, and the main performance parameters of the optical fibers of Comparative Example 1 and Examples 1-2 are shown in Table 3 below.

[0129] Table 1 Correlation data between the content of different element-doped optical fibers and the relative refractive index and fictive temperature

[0130]

[0131] From Table 1, we can observe that the present application not only reduces the fictive temperature but also significantly improves the refractive index by co-doping the fiber core with chlorine and bromine elements.

[0132] Table 2 Refractive index profile parameters of Comparative Example 1 and Examples 1-2

[0133]

[0134] Table 3 Main performance parameters of optical fibers of Comparative Example 1 and Examples 1-2

[0135]

[0136] From Table 2-3, we can observe that as the content of doped Br changes, the attenuation performance of the optical fiber at a wavelength of 1550nm will be optimized as the Br doping content increases. This application meets the application requirements of low-attenuation optical fiber by co-doping the fiber core with chlorine and bromine elements.

[0137] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all various changes or equivalent substitutions falling within the scope of the claims of the present application are included. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present invention.

Claims

1. A low-loss optical fiber, characterized in that: include: A core portion of the central axis and an outer sleeve surrounding the core portion, the refractive index of the outer sleeve area is lower than the refractive index of the core portion area, the core portion is co-doped with chlorine and bromine elements, and the total content of doped elements in the core portion is 1.5wt% to 5wt%.

2. The low-loss optical fiber according to claim 1, characterized in that: The bromine doping content in the core portion accounts for 0.1 to 40% of the total doping element content.

3. The low-loss optical fiber according to claim 1, characterized in that: The outer cladding tube comprises: an inner cladding and an outer cladding surrounding the inner cladding, the refractive index of the inner cladding region is lower than the refractive index of the core region, and the refractive index of the outer cladding region is higher than the refractive index of the inner cladding region and lower than the refractive index of the core region.

4. The low-loss optical fiber according to claim 3, characterized in that: The inner cladding layer comprises: fluorine-doped silica glass and / or bromine-doped silica glass, and the outer cladding layer comprises: fluorine-doped silica glass.

5. The low-loss optical fiber according to claim 3, characterized in that: The relative refractive index difference Δ1 of the core region is 0% to 0.3%, and the radius R1 of the core region is 5 to 15 μm; the relative refractive index difference Δ2 of the inner cladding region is 0 to -0.25%, and the radius R2 of the inner cladding region is 15 to 45 μm; the relative refractive index difference Δ3 of the outer cladding region is 0 to -0.15%, and the radius R3 of the outer cladding region is 40 to 120 μm.

6. The low-loss optical fiber according to claim 5, characterized in that: The difference between the relative refractive index difference △2 of the inner cladding region and the relative refractive index difference △1 of the core region is 0.2% to 0.4%, and the difference between the relative refractive index difference △3 of the outer cladding region and the relative refractive index difference △1 of the core region is 0.1% to 0.4%.

7. The low-loss optical fiber according to claim 1, characterized in that: The attenuation coefficient of the optical fiber at a wavelength of 1550nm is ≤0.165dB / km, and the mode field diameter of the optical fiber at a wavelength of 1550nm is 12.0um-13.0μm.

8. A method for preparing a low-loss optical fiber, wherein the low-loss optical fiber according to any one of claims 1 to 7 is prepared, characterized in that: The following steps are involved: S1 prepares a SiO2 substrate by a vapor phase axial deposition process to obtain a SiO2 substrate; S2 exposes the SiO2 substrate to a mixed atmosphere of a SiBr4 dopant precursor and a SiCl4 dopant precursor, performs doping treatment on the SiO2 substrate body before the SiO2 substrate is completely densified, and finally sintering and densifying, and annealing to obtain a chlorine and bromine co-doped core portion; S3: inserting the fiber core part co-doped with chlorine and bromine into an outer sheath to obtain an optical fiber preform rod that can be used for drawing, and drawing the optical fiber preform rod that can be used for drawing to form a low-loss optical fiber.

9. The method for preparing a low-loss optical fiber according to claim 8, characterized in that: In step S2, the SiO2 substrate is exposed to a mixed atmosphere of a SiBr4 dopant precursor and a SiCl4 dopant precursor for doping treatment for 1 to 1.5 hours.

10. The method for preparing a low-loss optical fiber according to claim 8, characterized in that: In step S3, the optical fiber preform rod available for drawing is drawn at a drawing speed of 1000m / min to 2000m / min, and the drawing tension is 150g to 200g.